Study of Language and Linguistics in Teacher Education Programmes Implications for Teacher Development - PATRA, KRUSHNA CHANDRA; BASANTIA, TAPAN KUMAR (INDIAN EDUCATIONAL REVIEW, 2025)
A teacher education programme is pertinent to build the competencies and skills of teachers in language and linguistics. So, a study of language and linguistics in teacher education programmes was conducted on the following objectives: (i) to analyse the status of study of language and linguistics in the course structure for NCTE two-year B.Ed. programme, and (ii) to analyse the status of the study of language and linguistics in curriculum of B.Ed. programme of three universities, and RIE Bhubaneswar. The study was based on document analysis of language and linguistics components of twoyear B.Ed. programme, and four-year Integrated B.A. B.Ed./B.Sc. B.Ed. programme based on Appendix-4 and Appendix-13 of NCTE, New Delhi. The documents studied were curriculum framework of two-year programme of NCTE, New Delhi and the course structure or its associated documents of two-year B.Ed. programme and a four-year integrated B.A. B.Ed./B.Sc. B.Ed. programme under three universities. The findings of the study indicated that course structure for NCTE two-year B.Ed. programme provides guidelines for inclusion of language in curriculum of B.Ed. programme of different universities and institutions of the country. It was also found that language components studied in B.Ed. programmes of the universities and institutions are largely based on the guidelines of course structure for NCTE two-year B.Ed. programme with some variations. The study has implications for strengthening the language and linguistics components in teacher education programmes in the context of teacher development.